Respostas

2014-07-29T13:08:40-03:00
Oi gata,

use as propriedades da exponenciação

a^{m+n}~\to~a^m*a^n\\\\
 a^{-m}~\to~\dfrac{1}{a^m}

em seguida ponha    3^x    em evidência:

3^x+3^{x+1}-3^{x-1}= \dfrac{11}{9}\\\\
3^x+3^x*3^1-3^x*3^{-1}= \dfrac{11}{9}\\\\
3^x(1+3^1-3^{-1})= \dfrac{11}{9}\\\\
3^x\left(1+3- \dfrac{1}{3^1}\right)= \dfrac{11}{9}\\\\
3^x\left(4- \dfrac{1}{3}\right)= \dfrac{11}{9}\\\\
3^x* \dfrac{11}{3}= \dfrac{11}{9}\\\\
3^x= \dfrac{11}{9}* \dfrac{3}{11}\\\\
3^x= \dfrac{33}{297}\\\\
3^x= \dfrac{33:33}{297:33}\\\\
3^x= \dfrac{1}{9}\\\\
3^x= \dfrac{1}{3^2}\\\\
\not3^x=\not3^{-2}\\\\
x=-2\\\\\\
\boxed{S=\{-2\}}

Tenha ótimos estudos =))
1 5 1